How economic recession effect the corporate philanthropy? Evidence from Pakistani corporate sector - Zulfiqar, Sehar (Applied Studies in Agribusiness and Commerce, 2017)
Corporate philanthropy is a significant indicator of firm’s socially responsible behavior. Researchers and managers acknowledge the immense potential of corporate philanthropy for optimizing social and economic benefits. Aligned with this view corporate sector in Pakistan is engaged in philanthropic initiatives in some form or another. This paper aims to present the response of the Pakistani corporate sector to the corporate philanthropy at the time of global economic recession 2008-2009 by analyzing the sample of Public Listed Companies (PLCs). The analysis revealed that during the global financial crisis, the economic condition of Pakistan was worsened that was already in distress, but it hasn’t strongly effected the corporate philanthropy as the data shows a slight decrease in the overall volume of corporate donations in 2007 and a slight decrease in the number of companies engaged in philanthropy during 2008. The finding of the study suggests that during the global economic downturn the PLCs in Pakistan continued to show commitment towards community through corporate donations. JEL code: B22